Development and usability testing of a chatbot to promote mental health services use among individuals with eating disorders following screening. Issue 9 (18th August 2022) - Shah, Jillian; DePietro, Bianca; D'Adamo, Laura; Firebaugh, Marie‐Laure; Laing, Olivia; Fowler, Lauren A.; Smolar, Lauren; Sadeh‐Sharvit, Shiri; Taylor, C. Barr; Wilfley, Denise E.; Fitzsimmons‐Craft, Ellen E.
Abstract: Objective: A significant gap exists between those who need and those who receive care for eating disorders (EDs). Novel solutions are needed to encourage service use and address treatment barriers. This study developed and evaluated the usability of a chatbot designed for pairing with online ED screening. The tool aimed to promote mental health service utilization by improving motivation for treatment and self‐efficacy among individuals with EDs. Methods: A chatbot prototype, Alex, was designed using decision trees and theoretically‐informed components: psychoeducation, motivational interviewing, personalized recommendations, and repeated administration. Usability testing was conducted over four iterative cycles, with user feedback informing refinements to the next iteration. Post‐testing, participants (N= 21) completed the System Usability Scale (SUS), the Usefulness, Satisfaction, and Ease of Use Questionnaire (USE), and a semi‐structured interview. Results: Interview feedback detailed chatbot aspects participants enjoyed and aspects necessitating improvement. Feedback converged on four themes: user experience, chatbot qualities, chatbot content, and ease of use. Following refinements, users described Alex as humanlike, supportive, and encouraging. Content was perceived as novel and personally relevant. USE scores across domains were generally above average (~5 out of 7), and SUS scores indicated "good" to "excellent" usability across cycles, with the final iteration receiving the highest average score. Discussion: Overall, participants generally reflected positively on interactions with Alex, including the initial version. Refinements between cycles further improved user experiences. This study provides preliminary evidence of the feasibility and acceptance of a chatbot designed to promote motivation for and use of services among individuals with EDs. Public Significance: Low rates of service utilization and treatment have been observed among individuals following online eating disorder screening. Tools are needed, including scalable, digital options, that can be easily paired with screening, to improve motivation for addressing eating disorders and promote service utilization.